CircRNA-protein complexes: IMP3 protein component defines subfamily of circRNPs - Schneider, Tim; Hung, Lee-Hsueh; Schreiner, Silke; Starke, Stefan; Eckhof, Heinrich; Rossbach, Oliver; Reich, Stefan; Medenbach, Jan; Bindereif, Albrecht; Justus Liebig University Giessen (My University, 2016)
Circular RNAs (circRNAs) constitute a new class of noncoding RNAs in higher eukaryotes generated from pre-mRNAs by alternative splicing. Here we investigated in mammalian cells the association of circRNAs with proteins. Using glycerol gradient centrifugation, we characterized in cell lysates circRNA-protein complexes (circRNPs) of distinct sizes. By polysome-gradient fractionation we found no evidence for efficient translation of a set of abundant circRNAs in HeLa cells. To identify circRNPs with a specific protein component, we focused on IMP3 (IGF2BP3, insulin-like growth factor 2 binding protein 3), a known tumor marker and RNA-binding protein. Combining RNA-seq analysis of IMP3-co-immunoprecipitated RNA and filtering for circular-junction reads identified a set of IMP3-associated circRNAs, which were validated and characterized. In sum, our data suggest that specific circRNP families exist defined by a common protein component. In addition, this provides a general approach to identify circRNPs with a given protein component.
Keywords: ddc:540